Political Conflict on the Results of Recapitulation in Regional Head Elections in North Borneo Province in 2015 - Saputra, Herdin Arie; Setiawan, Anang; Nofrima, Sanny; Muksin, Dafrin (ARISTO, 2022)
The conflict that occurred amid the people of North Borneo Province in the Regional Head Election for the first time in 2015 was the non-acceptance of one of the candidate's supporters after the recapitulation of the vote count. Demonstrations of facilities damage conflicts include burning the Governor's office, burning of the Regional Election Commission (KPUD) office, banners, burning tires, and burning cars. This study uses qualitative research methods with a phenomenological approach, in data collection with in-depth interviews with resource persons including Chairperson of Regional Election Commission (KPUD), Commissioner of Regional Election Commission (KPUD), Members of Regional Election Commission (KPUD), and Regency Communities Bulungan. This research is also inseparable by collecting books, journals, reputable websites, and the like related to research. Furthermore, the data is managed using the Nvivo 12 Plus software, with Crosstab Analysis feature in common sentences, then concluded. The results showed that the trigger for the reaction that resulted in the conflict was due to regional sentiment, indicating that there was an indication of money politics, the state civil apparatus (ASN), and the lack of C6 forms.